Die gebruik van Eksodus 19–24 in 1 Petrus 1:2 – ’n Eksegetiese ondersoek - Douw G. Breed (In die Skriflig)
The use of Exodus 19–24 in 1 Peter 1:2 – An exegetical investigation. 1 Peter shows an exceptional number of quotations from and references to the Old Testament. Although much has already been written about the author of 1 Peter’s use of the Old Testament, little attention is given to the possibility that the author already has the Old Testament in mind in 1 Peter 1:2. This article investigates whether Peter, with the three prepositional phrases in 1:2, has specific Old Testament passages in mind. Greater clarity regarding Peter’s intention with the three prepositional phrases in 1:2 is achieved by placing the phrases within the context of 1 Peter. It is then examined whether Peter refers to specific Old Testament passages with each of the three phrases. The grammatical-historical model of exegesis, as practiced within the Reformed tradition, is followed in this article. Peter’s three prepositional phrases in 1:2 refer to the covenant events as described in Exodus 19–24. With the prepositional phrase κατὰ πρόγνωσιν θεοῦ πατρὸς, he refers to God’s redemptive plan as outlined in Exodus 19:3–8. The prepositional phrase, ἐν ἁγιασμῷ πνεύματος, reflects both God’s holiness and Israel’s holiness as recorded in Exodus 19–24. The prepositional phrase, εἰς ὑπακοὴν καὶ ῥαντισμὸν αἵματος Ἰησοῦ Χριστοῦ, refers to Israel’s obedience and the confirmation of the covenant between God and Israel as described in Exodus 24:3–8.